Canine Leproid Granuloma in Mineiros City Mid-West Region of Brazil - Ribeiro, Debora da Silva Freitas; da Silva, Jhosani Beatriz Bispo; Saldanha, Tatiane Souza; Bezerril, Juliana Evangelista; Ribeiro, Rodrigo Martins (Acta Scientiae Veterinariae, 2021)
Background: Among the bacterial dermopathy the canine leproid granuloma (CLG) is a nodular pyogranulomatous disorder that affects the skin or subcutaneous tissue mainly in the dorsal face of ear pinna, head, and extremity of members caused by Mycobacterium spp. The pathogenicity is still not well clarified regarding the causative agent, which has not yet been completely typified, but phylogenetically, it is related to Mycobacterium tilburgii, M. simiae, and M. genavense, in Brazil, by the species M. murphy. The objective of this study is to report a case of canine leproid granuloma, through cytology and histopathology, and present the therapeutic procedures until the regression of cutaneous lesion. Case: A 5-year-old Boxer breed, intac male weighing 32 kg, was assisted at the Veterinary Clinic of UNIFIMES, in Mineiros City, Mid-West Region of Brazil, GO, Brazil. The animal had 4 nodules in the ears with evolution of 30 days, with no pruritus and without previous treatment. During the physical exam, the animal had normal physiological parameters. The cutaneous lesions were characterised by papules and alopecic nodules of firm to fibroelastic consistency, with progressive increase, located in the convex face of the ears. The fine needle aspiration puncture technique (FNAP) and histopathology for a definitive diagnosis was used, allowing the differentiation between inflammatory processes, infectious and neoplastic. Furthermore, blood was collected for hemogram and biochemical analysis for the assessment of renal and hepatic functions. In cytology, the stained blades by the Diff-quick stain in the microscopic exam had elevated cellularity, with several macrophages, and bacilliform structures in the negative image. Staining was also conducted by the Ziehl-Neelsen technique, which showed the presence of alcohol-acid-resistant bacilli (AARB) inside macrophages and in the centre of granuloma. In the animal’s follow up, a punch biopsy for histopathologic was conducted. A predominance of macrophages of epithelioid appearance, which were localised in the centre of nodulations, variable quantities de-agglomerates of degenerated neutrophils, was observed. In the periphery of the lesion intense infiltrate of lymphocytes and plasmocytes was found. Based on the clinical history, in the physical exam and laboratory findings, a treatment for mycobacteriosis with oral enrofloxacin 10 mg/kg every 24 h associated to doxycycline 10 mg/kg every 24 h and rifampicin topical twice a day in the cutaneous lesions was initiated. After three months of treatment, the animal did not have collateral effects with the association of antibiotics and had a complete clinical resolution, without recurrence. Discussion: Despite that the CLG etiopathogeny is not well clarified, it is important to highlight the involvement of insects, such as flies and mosquitoes, inoculating the mycobacteria. Despite the fact that large size dogs, of breeds with short hair that are raised outdoors, have greater susceptibility to CLG and the lesions can be located specially in the face and ears, it is recommended to use complementary exams, such as cytology and histopathology, to obtain a definitive diagnosis. The CLG is a disease already reported in some regions of the Brazilian territory; however, it is believed that it is underdiagnosed, making it difficult to effectively use the therapeutic protocol.